The Impact of Vitamin D Deficiency on Population Health: Assessment, Monitoring, and Intervention Strategies - Alhulayyil, Alanoud Abduallh; alonzay, Hessa trad; Alshammari, Mohammed Habbas Mater; Alanzi, Sarah Saab; Al Harbi, Fahad Muzil O; Qunfuthi, Wed Suliaman; Ghbri, Mohammed Ahmed; Zaylaee, Raed Jameel Mohammed; Yahya, Falah Awad Shaker; Alqarni, Ali Murdi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Vitamin D is an essential fat‑soluble hormone involved in calcium and phosphate homeostasis, bone mineralization, and multiple extra‑skeletal physiological processes. Despite advances in nutrition and food fortification, vitamin D deficiency remains a major global public health problem, affecting diverse populations and contributing to significant morbidity. Aim: This review aims to assess the global burden of vitamin D deficiency, examine its etiology, pathophysiology, clinical manifestations, and evaluate current strategies for assessment, monitoring, prevention, and management. Methods: A narrative synthesis of epidemiological data, clinical outcomes, diagnostic criteria, and therapeutic approaches to vitamin D deficiency was conducted, incorporating evidence from observational studies, clinical trials, and international guidelines discussed in the literature. Results: Vitamin D deficiency affects approximately one billion individuals worldwide, particularly older adults, obese individuals, hospitalized patients, and those with limited sun exposure. Deficiency is linked to skeletal disorders such as rickets and osteomalacia, increased fracture risk, muscle weakness, and potential non‑skeletal complications. Vitamin D3 supplementation is superior to vitamin D2 in correcting deficiency and maintaining adequate serum levels. Conclusion: Targeted screening, individualized supplementation, and interprofessional healthcare strategies are essential to reduce the burden of vitamin D deficiency and its complications.